Locating, understanding and celebrating disability: Revisiting Erikson's "stages". (August 2018) - Jordan, Karen; Tseris, Emma
The assumption of universal human developmental tasks is central to Erikson's influential Eight Stages of Man . While grand developmental theories have been strongly critiqued from a feminist perspective, it is necessary for feminists to also consider the implications of Erikson's theory from a critical disability perspective. Applications of Erikson's theory have claimed that disabled people experience stagnated development because they are unable to complete the achievements required for full participation in adulthood. However, we argue that the positioning of disabled people as diminished adults is open to question, as it is based on narrowly defined notions of "autonomy", "industry" and "initiative". Additionally, constructions of disabled adults as "dependent" or "vulnerable" render invisible the systematic exclusion of disabled people from social and economic opportunities. Human service workers who adopt normative developmental understandings may not realize the potential for "well-intentioned" disability services to cause harm through paternalism and a culture of low expectations. It is essential that universalized models of adulthood are deconstructed from both feminist and critical disability perspectives, in order to locate, understand and celebrate diverse developmental experiences. We offer some ideas about how this deconstruction might be enacted within a university education context.